PERENCANAAN JALUR EVAKUASI BENCANA TSUNAMI DALAM MENUNJANG ASPEK KESELAMATAN PADA WISATA PANTAI CEMARA GADING, DESA SUKOJATI, KECAMATAN BLIMBINGSARI - Safitri, Fikca Ayuk; Satyaning Budhi, Wahyu; Utanaka, Ahmad (Jurnal Abdimas Bina Bangsa, 2025)
Sukojati Village is one of the villages located in Blimbingsari District. The topography of Sukojati Village is lowlands and coastal areas. Directly bordering the Bali Strait to the east, causing people to live on the coast and work as fishermen. This also makes Sukojati Village have coastal tourism potential that can be developed continuously. This coast has great potential as a tourist attraction and brings economic development to the surrounding community. However, the area is also potentially vulnerable to disasters, especially tsunamis. Currently, there are no preventive measures against the tsunami disaster at Semara Gading Beach. Therefore, it is important to take preventive measures to minimize negative impacts, such as determining the location of evacuation routes at Cemara Gading Beach. This evacuation route is designed to reduce tsunami disasters by allowing local residents and tourists to evacuate from disaster-prone areas to safer areas. Therefore, it is important to take systematic disaster prevention measures at the tourist destinations you visit, such as providing tourist maps. To ensure the safety of tourists in areas where disasters such as tsunamis are expected, evacuation routes need to be planned and evacuation information provided in the event of a disaster is provided. This is expected to improve services to tourists, increase the number of tourist visits, and reduce the risk of death during a disaster.